Interleukin-12 family cytokines and sarcoidosis - Ringkowski, Sabine; Thomas, Paul S.; Herbert, Cristan (Frontiers in Pharmacology, 2014)
Sarcoidosis is a systemic granulomatous disease predominantly affecting the lungs. It is believed to be caused by exposure to pathogenic antigens in genetically susceptible individuals but the causative antigen has not been identified. The formation of non-caseating granulomas at sites of ongoing inflammation is the key feature of the disease. Other aspects of the pathogenesis are peripheral T-cell anergy and disease progression to fibrosis. Many T-cell-associated cytokines have been implicated in the immunopathogenesis of sarcoidosis, but it is becoming apparent that IL-12 cytokine family members including IL-12, IL-23, IL-27 and IL-35 are also involved. Although the members of this unique cytokine family are heterodimers of similar subunits, their biological functions are very diverse. Whilst IL-23 and IL-12 are pro-inflammatory regulators of Th1 and Th17 responses, IL-27 is bidirectional for inflammation and the most recent family member IL-35 is inhibitory. This review will discuss the current understanding of aetiology and immunopathogenesis of sarcoidosis with a specific focus on the bidirectional impact of IL-12 family cytokines on the pathogenesis of sarcoidosis.